2014
DOI: 10.12705/631.4
|View full text |Cite
|
Sign up to set email alerts
|

Independent evolutionary history between the Balkan ranges and more northerly mountains in Campanula alpina s.l. (Campanulaceae): Genetic divergence and morphological segregation of taxa

Abstract: Although the Balkan Peninsula belongs to the main European biodiversity centres, phylogeographical structure of its high‐mountain flora and relationships with adjoining mountain systems remain almost unknown. Here, we analyse the evolutionary patterns in Campanula alpina s.l., which comprises C. alpina Jacq. (eastern Alps, Carpathians) and the mostly neglected, allopatric Balkan taxon C. orbelica Pančić. Using a range‐wide sampling, two molecular marker systems (mostly nuclear AFLPs and chloroplast DNA sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…Populations from these two areas often share closely‐related genetic lineages (Ronikier et al ., ; Drag et al ., ; György et al ., ) and such affinities have been documented even for microbial communities in high‐mountain grasslands (Geremia et al ., ). Nevertheless, numerous cases of genetic divergence suggesting long‐term isolation of West Carpathians and Eastern Alps populations, often pre‐dating the last glaciation, have also been documented (Dzialuk et al ., ; Homburg et al ., ; Ronikier & Zalewska‐Gałosz, ; Pachschwöll et al ., ; Drees et al ., ; Frajman, Graniszewska & Schönswetter, ). It is difficult to correlate these divergent histories with features such as different dispersal potential of the taxa and they probably reflect individual histories of the species.…”
Section: Phylogeographical Patterns Biogeographical Barriers and Crymentioning
confidence: 96%
See 2 more Smart Citations
“…Populations from these two areas often share closely‐related genetic lineages (Ronikier et al ., ; Drag et al ., ; György et al ., ) and such affinities have been documented even for microbial communities in high‐mountain grasslands (Geremia et al ., ). Nevertheless, numerous cases of genetic divergence suggesting long‐term isolation of West Carpathians and Eastern Alps populations, often pre‐dating the last glaciation, have also been documented (Dzialuk et al ., ; Homburg et al ., ; Ronikier & Zalewska‐Gałosz, ; Pachschwöll et al ., ; Drees et al ., ; Frajman, Graniszewska & Schönswetter, ). It is difficult to correlate these divergent histories with features such as different dispersal potential of the taxa and they probably reflect individual histories of the species.…”
Section: Phylogeographical Patterns Biogeographical Barriers and Crymentioning
confidence: 96%
“…). This was substantiated in a later analysis of the same species, which showed that plastid DNA haplotypes from this area may constitute the most divergent intraspecific lineage (Ronikier & Zalewska‐Gałosz, ). The evolutionary importance of the south‐western edge of the Carpathians was recently supported by the phylogeographical structure of the montane plant Onobrychis transylvanica (Fabaceae; Băcilă et al ., ).…”
Section: Phylogeographical Patterns Biogeographical Barriers and Crymentioning
confidence: 97%
See 1 more Smart Citation
“…A further data set consisting of twenty-seven variant characters was prepared combining selected in vivo and herbarium characters and Pearson correlation coefficients (parametric) computed among all their pairs in order to check if any strong correlation (r0.80; p<0.01) existed that could potentially affect the results of further analyses (Dobeš et al 2013;Ronikier and Zalewska-Gałosz 2014). For not normally distributed variables, a Spearman correlation non-parametric method was applied (Šingliarová et al 2011).…”
Section: Descriptive and Univariate Analyses Of Morphometric Variationmentioning
confidence: 99%
“…In addition, some neglected or cryptic taxa have been reaffirmed: C. cichoracea Smith (Škondrić et al ., ); C. comosiformis (Hayek & Janch.) Frajman & Schneeweiss (Frajman & Schneeweiss, ); and C. orbelica Pančić (Ronikier & Zalewska‐Gałosz, ). Thus, it appears that the taxonomy of this genus has still not been explored satisfactorily and we expect an even greater number of taxa to be present in the Balkan Peninsula.…”
Section: Introductionmentioning
confidence: 99%